The trust deficit - Crosby, Sam (Carlton, Vic. : Melbourne University Publishing, 2016)
Trust is the most powerful weapon in the political arsenal. It can pierce an opponent's armour or deflect the most ferocious attack. It is the means through which difficult policies can be explained, a well of goodwill on which politicians can draw in their darkest hours. Yet despite its great value we are resigned to the idea that trust in politics will continue to decline. Drawing on contemporary political stories and examples, The Trust Deficit shows us how faith in our politicians has been eroded but how it can be rebuilt. By breaking trust down to its elements-reliability and competence, openness and honesty-we see how recent leaders established trust and used it to their political advantage.
Intro; Title; Copyright; Contents; Acknowledgements; 1 Carbon Taxes, Budgets, Molecules and Models; Part One: The Deficit; 2 Gillard's Carbon Tax: The Cost of Losing a Big Trust Gamble; 3 The Abbott Experiment: Underestimating the Potency of Trust; Part Two: Hope; 4 Consistency: The Long Memory of Authenticity; 5 Competence: Surfing a Financial Tsunami; 6 Openness: The Preacher and the President; 7 Honesty: The Surprising Power of Fessing Up; 8 Counterpoints and Conclusions; Notes; Index
Includes index.
eBooks on EBSCOhost
Keywords: Trust -- Political aspects -- Australia; Politicians -- Australia -- Public opinion; Political culture -- Australia; Political psychology -- Australia; Australia -- Politics and government -- Social aspects; Confiance -- Aspect politique -- Australie; Politiciens -- Australie -- Opinion publique; Psychologie politique -- Australie; Australie -- Politique et gouvernement -- Aspect social; Political culture; Political psychology; Politicians -- Public opinion; Politics and government -- Social aspects; Trust -- Political aspects; Australia; LITERARY CRITICISM; Electronic books